Social and relational identification as determinants of care workers’ motivation and well-being - Bjerregaard, Kirstien; Haslam, S. Alexander; Morton, Thomas; Ryan, Michelle K. (Frontiers in Psychology, 2015)
A growing body of research in the field of health and social care indicates that the quality of the relationship between the person giving care and the person receiving it contributes significantly to the motivation and wellbeing of both. This paper examines how care workers’ motivation is shaped by their social and relational identification at work. Survey findings at two time points (T1, N = 643; T2, N = 1274) show that care workers’ motivation increases to the extent that incentives, the working context (of residential vs. domiciliary care), and the professionalization process (of acquiring vs. not acquiring a qualification) serve to build and maintain meaningful identities within the organization. In this context care workers attach greatest importance to their relational identity with clients and the more they perceive this as congruent with their organizational identity the more motivated they are. Implications are discussed with regard to the need to develop and sustain a professional and compassionate workforce that is able to meet the needs of an ageing society.